Monitoring coronary blood flow by laser speckle contrast imaging after myocardial ischaemia reperfusion injury in adult and aged mice - El-Awaisi, Juma; Kavanagh, Dean P. J.; Kalia, Neena (Frontiers in Cardiovascular Medicine, 2024)
Introduction Investigating coronary microvascular perfusion responses after myocardial infarction (MI) would aid in the development of flow preserving therapies. Laser speckle contrast imaging (LSCI) is a powerful tool used for real-time, non-contact, full-field imaging of blood flow in various tissues/organs. However, its use in the beating heart has been limited due to motion artifacts. Methods In this paper, we report the novel use of LSCI, combined with custom speckle analysis software (SpAn), to visualise and quantitate changes in ventricular perfusion in adult and aged mice undergoing ischaemia-reperfusion (IR) injury. The therapeutic benefit of inhibiting the actions of the pro-inflammatory cytokine interleukin-36 (IL-36) was also investigated using an IL-36 receptor antagonist (IL-36Ra). Results Imaging from uncovered and covered regions of the left ventricle demonstrated that whilst part of the LSCI flux signal was derived from beating motion, a significant contributor to the flux signal came from ventricular microcirculatory blood flow. We show that a biphasic flux profile corresponding to diastolic and systolic phases of the cardiac cycle can be detected without mathematically processing the total flux data to denoise motion artifacts. Furthermore, perfusion responses to ischaemia and postischaemia were strong, reproducible and could easily be detected without the need to subtract motion-related flux signals. LSCI also identified significantly poorer ventricular perfusion in injured aged mice following IR injury which markedly improved with IL-36Ra. Discussion We therefore propose that LSCI of the heart is possible despite motion artifacts and may facilitate future investigations into the role of the coronary microcirculation in cardiovascular diseases and development of novel therapies.